The Oxford history of the classical world - Boardman, John 1924- .; Griffin, Jasper; Murray, Oswyn (Oxford, Eng. Oxford University Press, 1986)
Provides a historical framework of the Greco-Roman world focusing on the political and social history, literature, philosophy, the arts, etc.
Rome. The founding of the empire / David Stockton -- The arts of government / Nicholas Purcell -- Augustan poetry and society / R.O.A.M. Lyne -- Virgil / Jasper Griffin -- Roman historians / Andrew Lintott -- The arts of prose : the early empire / Donald Russell -- Silver Latin poetry and the Latin novel / Richard Jenkyns -- Later philosophy / Anthony Meredith -- The arts of living / Roger Ling -- Roman life and society / John Matthews -- Roman art and architecture / R.J.A. Wilson -- Envoi : on taking leave of antiquity / Henry Chadwick.
Includes bibliographical and index.
Keywords: Civilization, Classical